Water Dimer in CCl4 Investigated by In-Situ Infrared Spectroscopy and Computational Analysis - Lee, Jaejin (Archīum Ateneo, 2024)
The low solubility of solute molecules in a nonpolar solvent and the weak interactions between solute and solvent molecules can be utilized to study isolated solute molecules. The in-situ inclusion process of H2O and D2O in CCl4 was observed by infrared absorption spectroscopy. These in-situ spectra showed deviations from the monomer spectrum over time attributed to the formation of water dimers. The water dimer spectrum was extracted by subtraction between the time-series spectra. DFT calculations allowed the assignment of the four vibrational modes in the dimer spectrum. The most notable changes from the monomer to the dimer spectra were in the donor molecule, which showed a peak redshift and a large increase in the absorption strengths, especially for the donor OH (OD) bond which participates in the hydrogen bonding to the acceptor water molecule. Using free energy calculations, the equilibrium constants of H2O and D2O dimers dissolved in CCl4 were determined to be 0.013 and 0.015, respectively, and the concentrations were determined to be ∼1 μM. The intensity ratio between the v3 mode of the water monomer and the vBD mode of the dimer calculated through DFT was found to be in close agreement with the ratios from the monomer and dimer spectra. In contrast, when the solvent was chloroform, the increase of the vBD mode of the dimer from the experiment did not agree with that from the calculations, indicating that the specific interaction of the water molecules with chloroform should be considered.